Impaired everyday memory associated with encephalopathy of severe malaria: The role of seizures and hippocampal damage - Kihara, M; Carter, J; Holding, P; Vargha-Khadem, F; Scott, R; Idro, R; Fegan, G; De Haan, M; Neville, BG; Newton, C (2009)
Background. Seizures are common in children admitted with severe falciparum malaria and are associated with neuro-cognitive impairments. Prolonged febrile seizures are associated with hippocampal damage and impaired memory. It was hypothesized that severe malaria causes impaired everyday memory which may be associated with hippocampal damage. Methods. An everyday memory battery was administered on 152 children with cerebral malaria (CM) (mean age, 7 y 4 months [SD 13 months]; 77 males) 156 children (mean age, 7 y 4 months [SD, 14 months]; 72 males) with malaria plus complex seizures (MS) and 179 children (mean age, 7 y 6 months [SD, 13 months]; 93 males) unexposed to either condition. Results. CM was associated with poorer everyday memory [95% CI, -2.46 to -0.36, p = 0.004] but not MS [95% CI, -0.91 to 1.16, p = 1.00] compared to unexposed children. Children with exposure to CM performed more poorly in recall [95% CI, -0.79 to -0.04, p = 0.024] and recognition subtests [95% CI, -0.90 to -0.17, p = 0.001] but not in prospective memory tests compared to controls. The health factors that predicted impaired everyday memory outcome in children with exposure to CM was profound coma [95% CI, 0.02 to 0.88, p = 0.037] and multiple episodes of hypoglycaemia [95% CI, 0.05 to 0.78, p = 0.020], but not seizures. Discussion. The findings show that exposure to CM was associated with a specific impairment of everyday memory. Seizures commonly observed in severe malaria may not have a causal relationship with poor outcome, but rather be associated with profound coma and repeated metabolic insults (multi-hypoglycaemia) that are strongly associated with impaired everyday memory.